Aqueous extract from the Withania somnifera leaves as a potential anti-neuroinflammatory agent: a mechanistic study. Issue 1 (December 2016) - Gupta, Muskan; Kaur, Gurcharan
Abstract Background Microglial-mediated neuroinflammation is a key factor underlying the pathogenesis of various neurodegenerative diseases and also an important target for the development of the neuroinflammation-targeted therapeutics. Conventionally, the nonsteroidal anti-inflammatory drugs (NSAIDs) are prescribed, but they are associated with long-term potential risks. Natural products are the cornerstone of modern therapeutics, and Ashwagandha is one such plant which is well known for its immunomodulatory properties in Ayurveda. Methods The current study was aimed to investigate the anti-neuroinflammatory potential of Ashwagandha (Withania somnifera ) leaf water extract (ASH-WEX) and one of its active chloroform fraction (fraction IV (FIV)) using β-amyloid and lipopolysaccharide (LPS)-stimulated primary microglial cells and BV-2 microglial cell line. Iba-1 and α-tubulin immunocytochemistry was done to study the LPS- and β-amyloid-induced morphological changes in microglial cells. Inflammatory molecules (NFkB, AP1), oxidative stress proteins (HSP 70, mortalin), apoptotic markers (Bcl-xl, PARP), cell cycle regulatory proteins (PCNA, Cyclin D1), and MHC II expression were analyzed by Western blotting. Mitotracker and CellRox Staining, Sandwich ELISA, and Gelatin Zymography were done to investigate ROS, pro-inflammatory cytokines, and matrix metalloproteinase production, respectively. Ashwagandha effect on microglial proliferation, migration, and its apoptosis-inducing potential was studied by cell cycle analysis, migration assay, and Annexin-V FITC assay, respectively. Results ASH-WEX and FIV pretreatment was seen to suppress the proliferation of activated microglia by causing cell cycle arrest at Go/G1 and G2/M phase along with decrease in cell cycle regulatory protein expression such as PCNA and Cyclin D1. Inhibition of microglial activation was revealed by their morphology and downregulated expression of microglial activation markers like MHC II and Iba-1. Both the extracts attenuated the TNF-α, IL-1β, IL-6, RNS, and ROS production via downregulating the expression of inflammatory proteins like NFkB and AP1. ASH-WEX and FIV also restricted the migration of activated microglia by downregulating metalloproteinase expression. Controlled proliferation rate was also accompanied by apoptosis of activated microglia. ASH-WEX and FIV were screened and found to possess Withaferin A and Withanone as active phytochemicals. Conclusions The current data suggests that ASH-WEX and FIV inhibit microglial activation and migration and may prove to be a potential therapeutic candidate for the suppression of neuroinflammation in the treatment of neurodegenerative diseases.